Utilization of Android-Based Applications for Young Women In Dealing with Dysmenorrhea - Prita Devy Igiany; Arum Alfitasari; Rika Andriani; Julia Pertiwi; Arifatun Nisaa (Universitas Veteran Bangun Nusantara, 2025)
Menstruation is a natural process that all adolescent girls experience. However, many young women feel uncomfortable or experience dysmenorrhea during this time. The main issues surrounding this topic are the lack of information about dysmenorrhea, the underutilization of android applications, and the lack of training on how to use these applications for health purposes, specifically for dysmenorrhea. To address these problems, the proposed solutions include increasing awareness and understanding about dysmenorrhea and providing training on how to use android applications for health, specifically for dysmenorrhea. The goal of this activity is to utilize android-based health applications, such as menstrual cycle reminder apps, to help adolescent girls manage dysmenorrhea and continue with their daily activities. This activity was conducted with 410 students from MTS Negeri 1 Boyolali in grades VII and VIII. The implementation of this activity involves several stages, including socialization, training, technology application, mentoring, evaluation, and planning for program sustainability. The partners' knowledge and understanding were evaluated by comparing pretest and posttest results, which showed an average score increase of 26.2 from 58.18 to 84.34. The students' enthusiasm for participating in the activity was also high, as evidenced by their active participation and application of the knowledge gained. The follow-up plan that will be carried out based on the results of community service includes optimizing the role of the School Health Unit in improving the reproductive health of students through collaboration with local health centers. Keywords: Adolescent, Android, Dysmenorrhea